The effectiveness of wound caring technique with polyhexamethylene biguanide and dialkyl carbamoyl chloride to healing process duration of diabetic foot ulcer patient - Armi Armi; Dewi Fitriani; Mila Sartika; Yana Setiawan (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: Antimicrobial dressing on moist-based wound care is a successful wound care technique, especially for diabetes mellitus wounds. The moisture on wound can be made by closed wound care to reach a standard moisture in various wounds. The antimicrobial dressing type that can increase the wound healing is Polyhexamethylene biguanide (PHMB) and Dialkyl carbamoyl chloride (DACC). Polyhexamethylene biguanide can accelerate the tissue granulation and reduce the risk of infection. Dialkyl carbamoyl chloride is a part of moist wound healing with strong hydrophobic threat so the bacteria will be lifted and accelerate the wound healing process.  The aim of this research is to analyze the effect of healing technique  using Polyhexamethylene biguanide and Dialkyl carbamoyl chloride wound healing process on diabetic foot ulcer patients.